Alkaline phosphatase activity in the subtropical ocean: insights from nutrient, dust and trace metal addition experiments - Mahaffey, Claire; Reynolds, Sarah; Davis, Clare E.; Lohan, Maeve C. (Frontiers in Marine Science, 2014)
Phosphorus is an essential nutrient for all life on earth. In the ocean, the most bioavailable form of phosphorus is inorganic phosphate, but in the extensive subtropical gyres, phosphate concentrations can be chronically low and limit primary productivity and nitrogen fixation. In these regions, organisms produce hydrolytic enzymes, such as alkaline phosphatase (AP), that enable them to utilize the more replete dissolved organic phosphorus (DOP) pool to meet their cellular phosphorus demands. In this study, we synthesized data from 14 published studies and present our own findings from two research cruises (D326 and D361) in the eastern subtropical Atlantic to explore the relationship between AP activity (APA) and nutrients, Saharan dust and trace metals. We found that below a threshold phosphate concentration of ~ 30 nM, APA increased with an inverse hyperbolic relationship with phosphate concentration. Meanwhile, DOP concentrations decreased with enhanced APA, indicating utilization of the DOP pool. We found APA rates were significantly higher in the subtropical Atlantic compared to the subtropical Pacific Ocean, even over the same low phosphate concentration range (0 to 50 nM). While the phosphate concentration may have a first order control on the APA rates, we speculate that other factors influence this basin scale contrast. Using bioassay experiments, we show that the addition of Saharan dust and zinc significantly increased the rate of APA. To our knowledge, our results are the first direct field-based evidence that APA is limited by zinc in the subtropical ocean. Further work is required to explore the relationship between trace metals such as iron and zinc, which are co-factors of phosphohydrolytic enzymes, specifically PhoX and PhoA, respectively, and APA in the ocean.